2014
DOI: 10.1002/jbm.a.35377
|View full text |Cite
|
Sign up to set email alerts
|

Ternary composite scaffolds with tailorable degradation rate and highly improved colonization by human bone marrow stromal cells

Abstract: Poly(ε-caprolactone), PCL, is of great interest for fabrication of biodegradable scaffolds due to its high compatibility with various manufacturing techniques, especially Fused Deposition Modeling (FDM). However, slow degradation and low strength make application of PCL limited only to longer-term bioresorbable and non-load bearing implants. To overcome latter drawbacks, ternary PCL-based composite fibrous scaffolds consisting of 70-95 wt % PCL, 5 wt % Tricalcium Phosphate (TCP) and 0-25 wt % poly(lactide-co-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…The ALP activity was conversely correlated to total protein concentration, which suggests that differentiation was more advanced on scaffolds which supported cell proliferation to lesser extent. A similar trend was observed in the case of differentiation of MSCs within 3D polymeric and composite scaffolds produced by additive manufacturing [50,51]. It is worth noting that the TPC confirms the microscopic observations of the samples: the scaffolds with the smallest pores yielded the highest cell density and TPC.…”
Section: Resultssupporting
confidence: 81%
“…The ALP activity was conversely correlated to total protein concentration, which suggests that differentiation was more advanced on scaffolds which supported cell proliferation to lesser extent. A similar trend was observed in the case of differentiation of MSCs within 3D polymeric and composite scaffolds produced by additive manufacturing [50,51]. It is worth noting that the TPC confirms the microscopic observations of the samples: the scaffolds with the smallest pores yielded the highest cell density and TPC.…”
Section: Resultssupporting
confidence: 81%
“…To tune degradation rate without deterioration of initial mechanical properties of PCL, various concentrations of PLGA were attempted. The obtained ternary composite materials exhibited significantly increased tensile properties and degradation kinetics . Additionally, we observed significantly improved colonization by human mesenchymal stem cells, which make the ternary composites promising materials for fabrication of 3D scaffolds.…”
Section: Introductionmentioning
confidence: 72%
“…Neat PCL, binary composite PCL–TCP and ternary composites containing PCL, TCP, and PLGA in quantities given in Table were prepared by means of a solvent casting technique as previously described . Briefly, polymers were dissolved in methylene chloride and TCP was dispersed in the polymer solution.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are some studies performed in order to gain better control on this process. For example, it was shown that the addition of poly(lactic‐co‐glycolic acid) as the third phase in the PCL‐based composites may increase the degradation rate (Idaszek et al ., ). At the same time TCP did not significantly influence the degradation rate of the scaffold (Idaszek et al ., ).…”
Section: Discussionmentioning
confidence: 97%